Anesthesia effects of different doses of fospropofol disodium for painless colonoscopy diagnosis and treatment - Yue, Fangli; Shi, Xinyuan; Ji, Ruoyi; Wei, Yaxin; Xiao, Hongyi; Zhang, Huan; Fu, Min; Ji, Fanceng (Frontiers in Medicine, 2025)
PurposeTo explore the clinical anesthesia effect of different doses of fospropofol disodium for painless colonoscopy.Patients and methodsA total of 69 patients undergoing colonoscopy under general intravenous anesthesia were included in this study. They were divided into three groups: fospropofol disodium 10 mg/kg group (P1 group, n = 23), fospropofol disodium 12.5 mg/kg group (P2 group, n = 23), and fospropofol disodium 15 mg/kg group (P3 group, n = 23). All patients were first injected with 5 μg/kg of alfentanil intravenously at the time of anesthesia induction, 1 min later, group P1, group P2 and group P3 were given 10 mg/kg, 12.5 mg/kg and 15 mg/kg of fospropofol disodium, respectively. The success rate of the first sedation, the time of sedation start, the time of awakening, hemodynamic changes and adverse reactions were recorded.ResultsThe success rate of first sedation in the P2 and P3 groups was significantly higher than that in the P1 group (p < 0.05). The onset time of sedation was significantly shorter in the P2 and P3 groups than in the P1 group (p < 0.05). The awakening time of the P2 group and the P3 group (9 min vs. 7 min) was significantly longer than that of the P1 group (5 min) (p < 0.05). The incidence of hypotension in the P3 group was significantly higher than that in the P1 and P2 groups (p < 0.05). At T2, the MAP of the P3 group decreased significantly compared with the P1 and P2 groups (p < 0.05). There were no significant differences in adverse reactions such as injection pain, abnormal sensation/itching between the three groups (p > 0.05).ConclusionIn painless colonoscopy, fospropofol disodium 12.5 mg/kg combined with alfentanil 5 μg/kg has a high success rate of first-time sedation and low hemodynamic impact, which has some clinical advantages.Clinical trial registrationChiCTR2400090788.